2017
DOI: 10.1186/s12944-017-0514-6
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid regulates vascular endothelial cell function and prevents cardiovascular disease

Abstract: Docosahexaenoic acid (DHA) is present in high concentrations in salmon, herring, and trout. Epidemiologic studies have shown that high dietary consumption of these and other oily fish is associated with reduced rates of myocardial infarction, atherosclerosis, and other ischemic pathologies. Atherosclerosis is induced by inflammation and can lead to acute cardiovascular events and extensive plaque. DHA inhibits the development of inflammation in endothelial cells, alters the function and regulation of vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 113 publications
4
38
0
Order By: Relevance
“…In line with our result, Yu et al claimed that the down-regulation of cyclooxygenase-2 was responsible for the declined level of PGE 2 after treatment with DHA 27. Docosahexaenoic acid had potential to increase the NO level, which is thought to be essential in vasodilation and endothelial haemostasis and protection 30,31. We also noted a profound reduction in NO level in Pal-treated cells, showing dysregulated NO synthesis inside endothelial lineage.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In line with our result, Yu et al claimed that the down-regulation of cyclooxygenase-2 was responsible for the declined level of PGE 2 after treatment with DHA 27. Docosahexaenoic acid had potential to increase the NO level, which is thought to be essential in vasodilation and endothelial haemostasis and protection 30,31. We also noted a profound reduction in NO level in Pal-treated cells, showing dysregulated NO synthesis inside endothelial lineage.…”
supporting
confidence: 91%
“…Docosahexaenoic acid had potential to increase the NO level, which is thought to be essential in vasodilation and endothelial haemostasis and protection. 30,31 Our study further demonstrated that Pal could increase the expression of eNOS and PTX3 genes, causing nitro-oxidative or nitrosative stress. 32,33 It was previously stated that eNOS activation was initiated by omega-3 fatty acids like DHA by engaging Src/PI3kinase/Akt and MAPK signalling pathways.…”
Section: Dha Decreased Ptx3 and Inos Gene Expression In Atherosclersupporting
confidence: 53%
“…A diet rich in ω3 has since long been connected with maintaining cardiac and vascular health and preventing atherosclerosis [ 202 , 203 , 204 ]. Although some gaps in knowledge remain regarding the precise mode of action explaining the cardioprotective effects of EPA and DHA, several mechanisms have been proposed: preventing arrhythmias [ 205 , 206 ], lowering plasma triacylglycerol [ 207 ], preventing chronic intermittent hypoxia-induced atherosclerosis [ 208 ], decreasing arterial cholesterol delivery and preventing the formation of atherosclerotic plaques in arteries [ 209 ], regulating vascular endothelial cell function and improving vascular relaxation [ 210 ], decreasing platelet aggregation [ 211 ] and arterial inflammatory responses [ 212 ].…”
Section: The Roles Of Pufamentioning
confidence: 99%
“…Vasculature distributes in almost all organs and tissues and emerges a fundamental role in the function of organs and tissues [2]. Thus, vascular endothelial cell dysfunction has become a key factor in the occurrence and development of many diseases, including hypertension, coronary heart disease and other cardiovascular diseases [3,4]. Thrombosis caused by vascular endothelial injury is the pathological basis of many cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%